PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) BERBANTU FOTONOVELA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X MA BUSTANUL ULUM JAYASAKTI - Yoga Fajar R Prabowo; Wakijo Wakijo (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The effect of the project-based learning model (pjbl) assisted with photonovela on the learning outcomes of students in class x ma bustanul „ulum jayasakti in 2018/2019. The Fotonovela Project-Based Learning (PjBL) learning model is very suitable to be applied in learning economics because it is not enough to study and memorize economic concepts but it also requires an understanding and ability to solve economic problems properly. Through this learning model students can express their thoughts, exchange opinions, cooperate with each other if there are friends in the group who are experiencing difficulties. Obtained information in the form of odd semester results 2019/2020. In the learning outcomes there are still many students who have not met the minimum completeness criteria, namely 75 students learning outcomes in class X IPS 1, which achieved completeness, only 6 students. While those who did not reach the completeness were 19 students. In the hypothesis test that reads